Anti-sulfatide reactivity in patients with celiac disease. (3rd April 2017) - Saccomanno, Domenica; Tomba, Carolina; Magri, Francesca; Backelandt, Philippe; Roncoroni, Leda; Doneda, Luisa; Bardella, Maria Teresa; Comi, Giacomo Pietro; Bresolin, Nereo; Conte, Dario; Elli, Luca
Abstract: Objective: To explore a possible significance of the presence of anti-ganglioside and anti-sulfatide antibodies in sera of adult patients with celiac disease (CD) in different clinical scenario. Methods: We selected 22 adult patients with newly diagnosed CD and 20 age–sex matched non-CD controls. Patients' serum was tested – before and after at least 6 months on a gluten-free diet (GFD) – for anti-GM1, GM2, GM3, GD1a, GD1b, GD3, GT1a, GT1b, GQ1b and sulfatide IgM, IgG and IgA auto-antibodies, by means of a dot blot technique and enzyme-linked immunosorbent assay (ELISA). Results: We found the presence of auto-antibodies in untreated patients. In particular, anti-sulfatide IgG antibodies were present in 8 (36%) patients independently of the presence of neurological symptoms. Anti-sulfatide IgA antibodies were present in 3 (19%) patients. During GFD, anti-sulfatide IgG disappeared in all the patients, whereas IgA were observed in 2 patients. Anti-sulfatide, anti-GM1 and anti-GM2 IgM antibodies were also observed in 2 patients on a GFD. All the other auto-antibodies were absent and no demographic or clinical parameters were associated. Non-CD controls did not present any auto-antibody. Conclusions: We found anti-sulfatide IgG antibodies in CD patients on a gluten-containing diet. Anti-sulfatide IgA antibodies persisted during GFD together with the occurrence of other IgM auto-antibodies. These data suggest a possible link between gluten and IgG auto-antibodies.